ZOOM APPLICATION UTILIZATION IN DISTANCE LEARNING PROCESS DURING A PANDEMIC OF CORONAVIRUS (CASE STUDIES ON ELEMENTARY SCHOOL STUDENTS AT SD PRESIDEN YAYASAN PENDIDIKAN UNIVERSITAS PRESIDEN) - Sefchullisan . (Institut Pendidikan Tapanuli Selatan, 2022)
The Pandemic of Coronavirus in Indonesia has had a significant impact on several sectors such as the economy, industry, and education. The government also issued a policy regarding the existence of a distance learning process, this requires students and teachers to master technology. Several structures in education have changed due to policies during the pandemic, such as the implementation of the new academic year, the implementation of the learning process, and the use of school facilities for students. This distance learning must be carried out by every educational institution as a way for the learning process to continue. The author discusses thedistance learning process during the pandemic of Coronavirus. This case study illustrates the use of the Zoom application, which shows that all teachers and students at SD Presiden can operate the Zoom application so that all school activities run well.Another finding, SD Presiden developed another application called JIBAS. The JIBAS application is to support the distance learning process, especially when doing exams combined with the Zoom application as supervision by the teacher.